The reformation of rights: law, religion, and human rights in early modern Calvinism - Witte, John (Cambridge University Press, 2007)
John Calvin developed arresting new teachings on rights and liberties, church and state, and religion and politics that shaped the law of Protestant lands. Calvin's original teachings were periodically challenged by major crises - the French Wars of Religion, Dutch Revolt, the English Civil War, American colonization, and American Revolution. In each such crisis moment, a major Calvinist figure emerged - Theodore Beza, Johannes Althusius, John Milton, John Winthrop, John Adams, and others - who modernized Calvin's teachings and translated them into dramatic new legal and political reforms. This rendered early modern Calvinism one of the driving engines of Western constitutionalism. A number of basic Western laws on religious and political rights, social and confessional pluralism, federalism and constitutionalism, and more owe a great deal to this religious movement. This book is essential reading for scholars and students of history, law, religion, politics, ethics, human rights, and the Protestant Reformation.